Association of the genetic variants of luteinizing hormone, luteinizing hormone receptor and polycystic ovary syndrome - Liu Nana; Ma Yanmin; Wang Shuyu; Zhang Xiaowei; Zhang Qiufang; Zhang Xue; Fu Li; Qiao Jie (BMC, 2012)
Abstract Background High circulating luteinizing hormone (LH) level is a typical biochemical feature of polycystic ovary syndrome (PCOS) whose pathophysiology is still unclear. Certain mutations of LH and LH receptor (LHR) may lead to changes in bioactivity of these hormones. The aim of this study was determine the role of the LH and LHR polymorphisms in the pathogenesis of PCOS using a genetic approach. Methods 315 PCOS women and 212 controls were screened for the gene variants of LH G1052A and LHR rs61996318 polymorphisms by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). Results PCOS patients had significantly more A allele frequency of LH G1052A mutations than controls (p=0.001). Within PCOS group, carriers of LH 1052A allele had lower LH (p=0.05) and higher fasting glucose levels (p=0.04). No subjects were identified with LHR rs61996318 polymorphisms. A new LHR single nucleotide polymorphism (SNP) was found without clear association with PCOS. Conclusions Results suggested LH G1052A mutation might influence PCOS susceptibility and phenotypes.